2016
DOI: 10.1038/cdd.2016.143
|View full text |Cite
|
Sign up to set email alerts
|

Pellino-1 promotes lung carcinogenesis via the stabilization of Slug and Snail through K63-mediated polyubiquitination

Abstract: Pellino-1 is an E3 ubiquitin ligase acting as a critical mediator for a variety of immune receptor signaling pathways, including Toll-like receptors, interleukin-1 receptor and T-cell receptors. We recently showed that the Pellino-1-transgenic (Tg) mice developed multiple tumors with different subtypes in hematolymphoid and solid organs. However, the molecular mechanism underlying the oncogenic role of Pellino-1 in solid tumors remains unknown. Pellino-1-Tg mice developed adenocarcinoma in the lungs, and Pelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 46 publications
4
51
0
Order By: Relevance
“…6f). Peli1 is also reported to activate Akt [38,39], which is an important signaling in the regulation of neuropathic pain [40,41]. We found that knocking down Peli1 induced a significant reduction in Akt phosphorylation by 65.1% in the ipsilateral spinal cord, in comparison with scrambled shRNA control (Fig.…”
Section: Downregulation Of Peli1 Attenuates Cci-induced Mapk Phosphormentioning
confidence: 53%
“…6f). Peli1 is also reported to activate Akt [38,39], which is an important signaling in the regulation of neuropathic pain [40,41]. We found that knocking down Peli1 induced a significant reduction in Akt phosphorylation by 65.1% in the ipsilateral spinal cord, in comparison with scrambled shRNA control (Fig.…”
Section: Downregulation Of Peli1 Attenuates Cci-induced Mapk Phosphormentioning
confidence: 53%
“…1A). Probably, these DUBs might remove other ubiquitination events that have been associated with Snail1 stability, such as Snail1 K63 polyubiquitination mediated by Pellino E3 ligase (36) or A20-dependent Snail1 multimonoubiquitination (37).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of PELI1 increases cell proliferation and survival, and contributes to lung tumorigenesis by promoting the epithelial to mesenchymal transition. [ 49 ] Furthermore, PELI1 promotes cell survival and chemoresistance by upregulating the expression of cIAP2 in lung cancer. [ 50 ] Taken together, these findings suggest that PELI1 might be a potential therapeutic target in some tumor types.…”
Section: Discussionmentioning
confidence: 99%